The impact of discretion in the criminal justice system on animal cruelty prosecutions in Hong Kong - Whitfort, Amanda (Animal abuse and interpersonal violence, 2024)
Utilizing a database of animal cruelty prosecutions led by the police between 2013 and 2019, collated by the SPCA (Hong Kong), we examined how the use of prosecutorial and sentencing discretion has impacted animal abuse cases in Hong Kong. Less than 50% of animal cruelty cases investigated proceeded to trial despite animals being seized or the SPCA (HK) being asked to assist police. Analyzing data in 335 cases of active maltreatment, neglect, commercial exploitation, poisoning, trapping, and hoarding we found that the most common reasons for cases not to proceed to charge were inability of the police to identify the offender within the procedural time limits, subjective evaluations of whether an animal had suffered sufficiently for prosecution, and long-standing tolerance for certain kinds of offending. Where cases were proceeded with, low numbers of prosecutions, particularly for species other than dogs and cats, and perceptions that owners’ cruel acts were of lower culpability than those of strangers or those who had given up ownership of their animals significantly impacted sentencing decisions. Better recognition of the impact of gate-keeping decisions on animal cruelty cases would improve the administration of justice and allow for increased accountability of decision-makers in an area of significant public concern.